Motivational/Cultural Issues in the Utilization of Army Learning Model (ALM) Techniques While Instructing Armenian Soldiers - Brent Anders (Adult Education Research Conference, 2015)
Using Army Learning Model techniques to conduct a modified first-stage Sergeant’s course to Armenian soldiers, motivational and cultural issues were observed affecting learner experience/outcome. This action research observed that successful outcomes were achieved through specific use of facilitation, demo, and practical exercise instructional techniques, with firm control of class interactions.
Keywords: motivation; culture; Army learning model; ALM; facilitation